Best practice of individual competences in strategic leadership among principals of excellent secondary schools, Malaysia - Salleh, Mohamad Johdi; Mohamad, Nazifah Alwani (IJSRP.ORG, 2015)
The aim of the study is to investigate the best practice of Individual Competences in strategic leadership among principals of excellent secondary schools. The Model of Individual Competences of Strategic Leadership have been developed by Davies and Davies (2005, 2010), Preedy, Glatter & Wise (2007), Quong & Walker (2010), Nazifah (2012). The respondents of the study were thirty-six principals of excellent secondary schools in Selangor, Malaysia. The principals were asked to rate their practices using a five-point Likert scale ranging from 1 - not at all, and, 5 - frequently. It is interesting to discover that the most frequent practices for the component of ‘Restlessness’ were represented by two items ‘I always motivate members of the school organisation to continuously work hard for school excellence’ and ‘I always enlighten my desire to continuously increase my school development together with all members of the school organisation towards better level of excellence’ with same mean score of 4.7778. The most frequent practice of Absorptive Capacity was ‘I am always concerned with the latest information to increase my school excellence’ with mean score 4.6111. The component of Adaptive Capacity highest score was item ‘I am always ready to receive new ideas that can enhance the school excellence’ with the mean score of 4.7222. The most frequent practice of Wisdom item ‘I can tolerate the implementation of period of strategy but I am strict towards its achievement’ with mean score of 4.7222. It is hope that the research conducted amongst the excellent secondary schools principals would provide valuable insights into the strategic development processes and approaches towards the realization of Vision 2020 and Malaysian Education Blueprint 2013-2025.